Association among sperm chromatin condensation, sperm DNA fragmentation and 8‐OHdG in seminal plasma and semen parameters in infertile men with oligoasthenoteratozoospermia. (10th October 2021) - Hologlu, Dilara; Gunes, Sezgin; Asci, Ramazan; Henkel, Ralf; Guvenc, Tolga
Abstract: The present study aimed to investigate the clinical role of standard sperm diagnosis parameters (sperm concentration, motility, morphology) as well as aniline blue staining of histones, 8‐OHdG, TUNEL assay were performed on semen samples in infertile men with oligoasthenoteratozoospermia (OAT). Thirty‐two infertile and ten proven fertile men were included in the study. Chromatin condensation sperm in infertile men was significantly lower compared to the fertile men ( p < 0.0001). Age, sperm concentration, morphology and motility were significantly negatively correlated with chromatin condensation ( p < 0.05). However, no significant correlations among the chromatin condensation, SDF and sperm DNA damage were detected in terms of 8‐OHdG concentration.